Similarity in Indicators of Attractiveness in Heterosexual Couples, and their Relationship with Satisfaction and Trust - Pávez, Paula; Polo, Pablo; Valenzuela, Nohelia; Figueroa, Oriana; Rodríguez-Sickert, Carlos; Muñoz-Reyes, José Antonio (Psykhe, 2022)
In our species, the formation and maintenance of romantic partners is a nonrandom process. In this sense, similarity between members of the couple can be relevant for the beginning of the relationship (i.e., assortative mating) and maintenance, being similarity in attractiveness one of the most interesting aspects of this phenomenon. Despite that similarity in attractive traits has been documented, there is a lack of studies including modern morphological measures like fluctuating facial asymmetry or body fat percentage when assessing the effect that similarity in attractiveness could provoke on behaviors and feelings necessary to maintain a long-term relationship (e.g., satisfaction and trust). We assessed the presence of similarity in attractiveness for self-perceived measures (attractiveness and mate value) and physical traits (body fat percentage, body mass index, and fluctuating facial asymmetry) in a population of 196 heterosexual young couples from Chile (n = 392). Then, using actor-partner interdependence models (APIM), we assessed whether satisfaction and trust within the couples were influenced by attractiveness. Our results indicated the presence of similarity for all studied traits with the exception of fluctuating facial asymmetry. In addition, we only found that self-assessment of attractiveness is important for satisfaction in women, and partner's physical attractiveness is important for satisfaction and trust in men. Our results suggest that similarity in attractiveness is not playing a major role in affecting relationship. It is probably that similarity could be better explained from the initial stages of relationship, where the mating market forces conduce to the conformation of similar couples.